The thermal outdoor environment in track and field - best practices recommendations for minimizing risks - Gonzalez, J.; Lucero, D.; Barrera, P.; Endsley, B.; Ramos Jr, J.; Il-Oh, J. (NSCA Coach, 2021)
The purpose of this article is to help disseminate information on the thermal environment during track meets, risk management, and thermal reducing approaches coaches, athletes, and sports medicine personnel can employ for improved athletic performance in a hot environment.